GENDER-SPECIFIC INFLUENCE OF Aу MUTATION ON PROGENY METABOLIC PHENOTYPE, FETAL GROWTH AND PLACENTAL GENE EXPRESSION IN MICE - E. N. Makarova; E. I. Denisova; V. V. Kozhevnikova; A. E. Kuleshova (Вавиловский журнал генетики и селекции, 2018)
Obesity during pregnancy increases the risk of obesity in offspring. To correct the offspring development in obese mothers, it is necessary to reveal the molecular mechanisms that mediate the influence of the maternal environment on the offspring ontogenesis. Leptin levels increase with obesity. In C57Bl mice, the Ау mutation is associated with elevated blood levels of leptin in pregnant females and exerts a gender-specific effect on the metabolic phenotype of mature offspring. Aim: to study the influence of Ау mutation on sensitivity to diet-induced obesity in male and female offspring, on fetal and placental weight and on the expression of genes in the placentas of the fetuses of different sexes. Body weight and food intake on a standard and an obesogenic diet, fetal and placental weights on pregnancy days 13 and 18, and gene expression of glucose transporters (GLUT1, GLUT3), neutral amino acid transporters (SNAT1, SNAT2, SNAT4), insulin-like growth factor 2 IGF2 and its receptor IGF2R were measured in male and female offspring of и ɑ/ɑ (control) and Ау/ɑ mothers. Ay mutation influenced the body weight only in male offspring, which consumed a standard diet, and did not influence obesity development in both male and female offspring. The weight of fetuses and placentas in Ау/ɑ as compared to ɑ/ɑ  females was reduced on day 13 of pregnancy and was not different on day 18. On day 13 of pregnancy, the mRNA levels of the examined genes did not differ in placentas of male and female fetuses in ɑ/ɑ  females. In Ау/ɑ females, the gene expression of GLUT1, GLUT3, SNAT1 and SNAT4 was reduced in female placentas compared to male placentas. The results suggest that the sex-specific transcription response of placentas to elevated leptin levels in pregnant Ау/ɑ females can mediate the gender-specific impact of Ау mutation on the offspring metabolism in postnatal life.